Corporate governance attributes and firm value : evidence from Malaysia / Noirom Dony @ Fredolin Dony - Dony, Noirom Dony @ Fredolin (2015)
Contemporary corporate scandals and the East Asian financial crisis, other than that the latest global financial recession, is the consequence of incompetent corporate governance structures. In other word, this is contributed by lack of sound corporate governance due to separation of ownership and control that generates agency problems in the firms. In agency theory, the managers are expected to pursue their own interest rather than the shareholders' interest. This happens as shareholders are usually dispersed, therefore effecting adversely the capabilities to monitor and control managers' actions. It has been broadly recommended that corporate governance attributes develop suitable systems in the form of corporate performance and transparency. Therefore the purpose of this dissertation is to examine the firm value following the introduction of MCCG 2012 recommendations and to analyse and examine the relationship between corporate governance attributes and firm value using the agency theory. The corporate governance attributes examined namely on board size, outside directors, CEO duality and managerial ownership. The sample of this dissertation taken from the top 100 public listed firms on Bursa Malaysia based on their market capitalization. The data mining solely focussing on the corporate annual report as it is easily available, cost effective and minimum bias information. This dissertation discovered that the board size and outside directors are insignificant relationship with the firm value. On the other hand, CEO duality found to be positively and managerial ownership is negatively associated with the firm value. The findings imply that CEO duality suitable to a complex industry with intensifies competition and excessive managerial ownership will result adverse impact on firm value.